2022
DOI: 10.1002/nop2.1438
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events reported after first dose of SARS‐CoV‐2 vaccine in the Northern Region of Ghana

Abstract: Aim The study examined the associated adverse events following SARS‐CoV‐2 vaccination among healthcare workers during the first dose of the vaccine in the Northern Region of Ghana. Design The study was a cross‐sectional survey involving 463 healthcare workers. Method The data were collected using a structured questionnaire. The data were analysed descriptively, and binary logistics was performed using SPSS version 25. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…A systematic review reported that there was a wide range of hesitation about being vaccinated against COVID-19 among healthcare professionals around the globe, which ranged from 4.3% to 72.0% [ 13 ]. In most studies, concerns about the safety of the vaccine, its effectiveness, and the possibility of adverse reactions were identified as the primary factors contributing to COVID-19 among healthcare personnel [ 14 ]. However, vaccine acceptance increased among healthcare workers and the general population with the enforcement of trust in existing vaccines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review reported that there was a wide range of hesitation about being vaccinated against COVID-19 among healthcare professionals around the globe, which ranged from 4.3% to 72.0% [ 13 ]. In most studies, concerns about the safety of the vaccine, its effectiveness, and the possibility of adverse reactions were identified as the primary factors contributing to COVID-19 among healthcare personnel [ 14 ]. However, vaccine acceptance increased among healthcare workers and the general population with the enforcement of trust in existing vaccines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies concentrated exclusively on the effect of COVID-19 on HCW sleep [6,[10][11][12][13]. Stress and anxiety levels considerably rose, which had an adverse effect on sleep quality and self-efficacy [14,15].…”
Section: The Effect Of Covid 19 On Health Workersmentioning
confidence: 99%